Cultural integration in English material (a study on students’ vocabulary mastery and its effect on communication ability) - Lihawa, Kartin (English Education Department, 2023)
The objective of this study is to maximize SMA students’ mastery of English vocabulary which is to support and give the best effect on their ability in using English communication. To reach this objective is to treat the three English Department students of UNG in their English teaching practice based on cultural context of Gorontalo, in terms of improving the SMA students’ speaking ability which supported by their rich vocabularies. The method used in this program is qualitative and the technique to gather the data is observation of the teaching practice. The data derived from the 12 SMA students’ speaking ability to who were observed as they were the leaders of each of 12 groups from the 4 groups in each 3 classes handled by the three English Department students of UNG. The results show that applying cultural context material in teaching English can give positive effect in terms of improving SMA students’ ability in their communication in English.